Adaptive capacity to technological change: A microfoundational approach. (1st November 2016) - Aggarwal, Vikas A.; Posen, Hart E.; Workiewicz, Maciej
Abstract : Research summary> : We take a microfoundational approach to understanding the origin of heterogeneity in firms' capacity to adapt to technological change. We develop a computational model of individual‐level learning in an organizational setting characterized by interdependence and ambiguity. The model leads to organizational outcomes with the canonical properties of routines: constancy, efficacy, and organizational memory. At the same time, the process generating these outcomes also produces heterogeneity in firms' adaptive capacity to different types of technological change. An implication is that exploration policy in the formative period of routine development can influence a firm's capacity to adapt to change in maturity. This points to a host of strategic trade‐offs, not only between performance and adaptive capacity, but also between adaptive capacities to different forms of change . Managerial summary : Why are firms differentially effective at adapting to technological change? We argue that firms differ in the adaptive capacity of the routines that underlie their capabilities. These differences arise well before change occurs, and result because firms build routines that are differentially responsive to signals of performance decline associated with technological change. Thus, early managerial efforts to build superior productive efficiency must be complemented by efforts to build superior adaptive capacity. Our theory suggests that managers can prepare for technological change by implementing policies, in the formative period of organizational development, that promote individuals' exploration of novel actions. However, there are trade‐offs because preparation aimed at building adaptive capacity to one type of technological change may limit adaptive capacity to other types of change . Copyright © 2016 John Wiley & Sons, Ltd.